Rain Loads - Fanella, David A. (McGraw-Hill's AccessEngineering., 2021)
This Excel workbook determines rain loads in accordance with the 2018 IBC and ASCE/SEI 7-16. Rain load calculations are performed in imperial and metric units for roofs with drains, channel scuppers, closed scuppers, and circular scuppers.